2017
DOI: 10.1007/s00401-017-1789-4
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic hazard score: an enrichment marker for Alzheimer’s associated amyloid and tau deposition

Abstract: There is an urgent need for identifying nondemented individuals at the highest risk of progressing to Alzheimer’s disease (AD) dementia. Here, we evaluated whether a recently validated polygenic hazard score (PHS) can be integrated with known in vivo cerebrospinal fluid (CSF) or positron emission tomography (PET) biomarkers of amyloid, and CSF tau pathology to prospectively predict cognitive and clinical decline in 347 cognitive normal (CN; baseline age range = 59.7–90.1, 98.85% white) and 599 mild cognitively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 30 publications
5
108
0
Order By: Relevance
“…For that reason, early detection is critical to prevent progression of the disease [5,6]. A combined screening approach that integrates biomarker, genomic, and clinical information will likely be required to optimize early identification and prevention of AD progression [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, early detection is critical to prevent progression of the disease [5,6]. A combined screening approach that integrates biomarker, genomic, and clinical information will likely be required to optimize early identification and prevention of AD progression [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies excluded APOE and achieved AUC ranging from 0.57-0.75 [5,12,25,30]. Of those studies using time-to-event analysis, all four excluded APOE and reported hazard ratios (HR) ranging from 1.11-2.36 [23,35,70]. Of those studies using ORs, two included APOE in their PRS and reported OR ranging from 2.06-2.32 [12,34].…”
Section: Prediction Of Ad Case/control Statusmentioning
confidence: 99%
“…PRS is constructed as a weighted sum of allele counts, where the weights are the B‐coefficients of SNP association with the disease obtained with the Logistic Regression (LR) analysis. Recent development of a polygenic hazard score (PHS) approach goes beyond AD risk prediction and provides prediction of individual age‐specific risk for developing AD . Prior to PHS analyses, Desikan et al .…”
Section: Introductionmentioning
confidence: 99%